Mushroom Cultivators to Grow and Develop with Oyster Mushroom Cultivation Business in Perumnas Belimbing Kelurahan Kuranji Sub-District - Fiana, Risa Meutia; Febjislami, Shalati; Dewi Hayati, PK; Pramana Putra, Dian; Kurniadi, Deri (Andalasian International Journal of Social and Entrepreneurial Development, 2024)
The Belimbing Residential Area, which is densely populated and located near the market, has the potential to absorb the production of the Belimbing Youth Group's mushroom cultivation activities. However, since mushroom cultivation activities are still relatively new, the group needs help independently providing 100% mushroom-growing media (baglog) and seedling production.. The fresh oyster mushrooms they produce must be marketed immediately as they quickly spoil, and their quality decreases if stored for too long. Additionally, the need for knowledge in the post-harvest processing of oyster mushrooms is also a hurdle in developing the mushroom cultivation business of the Belimbing Youth Group. The primary objective of the community service activity is to enhance the abilities and experience of the Belimbing Youth Group in producing and processing mushroom cultivation products to create higher economic value. Initial outreach activities will focus on oyster mushroom seedling production and processing products, training on product processing and packaging techniques, entrepreneurial coaching, and further guidance, all forming part of technology transfer activities to the Belimbing Youth Group. In the first year, counselling and training on oyster mushroom seedling production, construction of a sterilization room, manufacture of baglog sterilization equipment, and repair of mushroom house (kumbung) were carried out. Training activities for producing F0 and F1 oyster mushroom seedlings and making baglog sterilization equipment with a capacity of 100 baglogs have impacted the independence of the Belimbing Youth Group in providing seedlings and baglog for oyster mushrooms. A sterilization room and repaired kumbung support the success of seeding and increasing the yield of oyster mushrooms. The success of the activities in the first year is likely to be sustainable and support the following year's activities, which will focus on post-harvest processing activities, packaging, and marketing of processed products.